(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Philosophy has an important role in the development of the Indian society. It is the character of the people which makes a society and nation strong. If the moral character and basic concepts of philosophy of people living in a society or country are not up to the mark then it is very difficult to maintain the development.Hence, philosophy and its related concepts are considered as the most important components of building the fundamental character of the people of the society. Philosophy has an immense power to change the mentality of the people which allows them to follow the positive things. The current paper highlights the significance of philosophy related to the development of Indian society.